2004
DOI: 10.1295/polymj.36.380
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Control of Curdlan (β-1,3-Glucan Polysaccharide) Provides Unique Polynucleotide Binding Properties

Abstract: ABSTRACT:Recently, we found that schizophyllan belonging to a -1,3-glucan polysaccharide family forms macromolecular complexes with certain single-stranded polynucleotides. The specific complex formation is originated from the -1,3-glucan skeleton in the main chain. In this paper, we have reported that curdlan, which is a -1,3-glucan polysaccharide without a side chain glucose unit, shows unique poly(C) binding properties different from those of schizophyllan; in the experiments using curdlan samples with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…37 Before the complexation study, therefore, we estimated the molecular weight from gel permeation chromatography (GPC). As shown in Table II, the molecular weights of the modified SPG derivatives are between M w ϭ 107,000 and 141,000, where the thermal stability is scarcely different from that of unmodified SPG [SPG(33.3)].…”
Section: Synthesismentioning
confidence: 99%
“…37 Before the complexation study, therefore, we estimated the molecular weight from gel permeation chromatography (GPC). As shown in Table II, the molecular weights of the modified SPG derivatives are between M w ϭ 107,000 and 141,000, where the thermal stability is scarcely different from that of unmodified SPG [SPG(33.3)].…”
Section: Synthesismentioning
confidence: 99%
“…Thus, understanding the relationship between the chain conformation and the mechanism of immunological activities becomes more and more important for biologists and polymer scientists. Recent findings have demonstrated that the denatured triple helical β‐glucans including schizophyllan (SPG), scleroglucan, and curdlan can interact with homo‐polynucleotide to form a novel complex with two single chains of β‐glucan and one single homo‐polynucleotide by a combination of hydrogen‐bonding and hydrophobic interactions under physiological conditions 5–8. The creation of new helical macromolecular complex consisting of DNA or RNA and polynucleotide can be widely used in gene delivery system and gene therapy, and would be an exciting development 9–12.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of glucans in the media depends on their chemical structure, molecular mass and conformation (Colleoni-Sirghie, Fulton, & White, 2003). The sulfate and phosphate esters of curdlan (Koumoto et al, 2004) with increased water solubility, display enhanced biological activity (Toida, Chaidedgumjorn, & Linhardt, 2003) and, moreover, a water-soluble aminated curdlan derivative has tumorigenic properties (Seijelid, 1986).…”
mentioning
confidence: 99%